The multifaceted regulatory effect of icariin on macrophages: a mini-review - Gao, Juan; Gao, Jin-Hong; Zhang, Yan-Fen; Gao, Da; Zhang, Ya-Peng (Frontiers in Immunology, 2026)
Macrophages are the major type of innate immune cells. They play important regulatory roles in tissue homeostasis, immune defense, and pathological progression across diverse diseases. Icariin (ICA), a bioactive flavonol glycoside isolated from the genus Epimedium, exhibits extensive therapeutic potential by targeting macrophages in various conditions. This review summarizes the regulatory effect of ICA on macrophages and the underlying mechanisms. Specifically, ICA exerts a context-dependent regulatory effect on macrophage polarization, metabolic reprogramming, autophagy, and crosstalk with other cells. Furthermore, the potential of ICA as a therapeutic agent for treating inflammation, cancers, bone-related disorders, and fibrotic diseases is discussed. The discussion focuses on macrophage-dependent mechanisms. To address poor aqueous solubility and targetability of ICA, various delivery systems have been developed. These systems include exosomes, hydrogels, nanoparticles, scaffolds, and inhalable micelles. Their main purpose is to enhance the macrophage-specific accumulation of ICA. Overall, this review provides a comprehensive framework for understanding the modulatory effects of ICA on macrophages. It may offer beneficial references for future research and development of ICA as an immunomodulator. Specifically, it serves as a reference for developing ICA to treat macrophage-mediated diseases.